Analysis of Factors Associated with Sexual Behavior among Adolescents in Tasikmadu District, Karanganyar Regency - Ananta Rinasari Kusumaningrum; Anisa Catur Wijayanti (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Adolescents are in a developmental phase characterized by significant biological, psychological, and social changes, potentially influencing various aspects of behavior, including sexual behavior. Limited understanding of reproductive health, exposure to pornographic content, the influence of the peer environment, and the suboptimal role of the family can increase adolescents' vulnerability to risky sexual behavior. Tasikmadu District, Karanganyar Regency, is one of the areas facing relatively high levels of adolescent reproductive health problems, so a scientific study is needed to identify factors of knowledge, attitudes, exposure to pornography, parental roles, and peer roles related to sexual behavior in the adolescent age group. Research Objective: to analyze factors of knowledge, attitudes, exposure to pornography, parental roles, and peer roles related to sexual behavior in Tasikmadu District, Karanganyar Regency. Method: The type of research used is quantitative analytic with a cross-sectional approach. The research sample was 193 respondents obtained using a purposive sampling technique. The independent variables include the level of knowledge, attitudes, exposure to pornography, parental roles, and peer influence, while the dependent variable is adolescent sexual behavior. Data collection was conducted through interviews and self-completed questionnaires by adolescents and analyzed using the Chi-Square test with a 95% confidence level. Results: The analysis results showed a relationship between the level of knowledge (p = 0.000), attitudes (p = 0.000), exposure to pornography (p = 0.000), parental influence (p = 0.047), peer influence (p = 0.039) with sexual behavior in adolescents. Conclusion: Adolescent sexual behavior is influenced by the interaction of individual, family, media, and social factors, so that prevention efforts require an integrated approach through education, family support, and strengthening a positive social environment.